Effects of Stream Channelization on Aquatic Macroinvertebrates, Buena Vista Marsh, Portage County, Wisconsin - Schmal, Robert N. (University of Wisconsin-Stevens Point, College of Natural Resources, 1978)
Objectives of this study were to assess effects of channelization on density and biomass of benthic and drifting macroinvertebrates, amount of drifting seston, and water temperature and chemistry in the Buena Vista marsh, Wisconsin. One-hundred meter sections of newly channelized (6-8 years old) and old channelized (52-62 years old) ditches and natural control streams from both upstream and downstream areas of the marsh were sampled between June 1974 and May 1975, and July 1975 and May 1976 at about 6-week intervals during ice-free periods. Substrate strongly influenced macroinvertebrate populations. Mean benthic density and biomass (excluding molluscs) from upstream and downstream areas were positively curvilinearly related to percentages of productive substrates (r = 0.89 and 0.69, respectively). Productive substrates, i.e., vegetation, silt detritus, and gravel, apparently provided interstices for entrapment of drifting seston resulting in negative relationships between seston and substrate (r = -0.76 and -0.87 for upstream and downstream sites, respectively). Productive substrates, discharge, drifting seston, and benthic populations together accounted for as much as 67% of the variation observed in drifting invertebrate density. Channelization affected macroinvertebrate populations by creating unstable substrate conditions during spring high flows, but created favorable vegetation and silt-detritus substrates as spring flows subsided and substrates stabilized. When vegetation and silt-detritus were predominant, invertebrate populations were high; when substrate was largely shifting sand and unstable silt-detritus, invertebrate populations were low. Newly channelized sites had higher benthic biomass and density than old ditches and natural streams except during unstable substrate conditions. The vegetation and silt-detritus in the ditches were favorable to snails (Gastropoda: Mollusca) and midges (Diptera: Chironomidae). Gastropods accounted for as much as 97% of mean benthic biomass in the upstream new ditch and Chironomidae up to 89% of mean benthic density in the downstream new ditch. More invertebrate taxa were collected from naturaJ streams, but differences were not statistically significant. However, stoneflies (Plecoptera) were only collected from natural streams, and more genera of mayflies (Ephemeroptera) and caddisflies (Trichoptera) were collected from natural streams than ditches. Channelized areas, with the exception of the downstream new ditLh, generally were devoid of depositional areas such as pools and point bars. The resulting reduced diversity of habitats in the ditches, especially during spoil bank instability and high spring flows, may have increased the amount of drifting seston when the more productive substrates were not present or not stable. Changes in amount of drifting seston at all sites seemed to correspond with changes in productive substrates and water level fluctuations. Channelization appeared to affect invertebrate drift through its influence on drifting seston and benthos. Increases in invertebrate drift upstream, especially Chironomidae, corresponded to increases in amount of seston (r = 0.71). Drift density at all sites downstream was significantly related to benthos density (r = 0.74). Numbers of drifting taxa were highest at sites with the highest percentages of sand substrate in their respective areas, the upstream old ditch and downstream natural stream. The downstream natural stream, despite low numbers of benthic taxa due to a predominantly shifting sand bottom, had significantly more invertebrate taxa in the drift than the downstream ditches. Water temperature and chemistry did not differ greatly among the natural streams and ditches, which receive approximately 90% of their flow from gound water. However, water temperature was generally higher in the ditches than in natural streams. Increases in water temperatures in the ditches may have resulted from removal of bank shading and slowing of flow. Water temperature exceeded 25°C (the 133-hr upper lethal temperature for brook trout, Salvelinus fontinalis for 5 consecutive days in the downstream new ditch in 1975. New and old channelized areas had higher alkalinity and total and calcium hardness than the natural streams.